Targeting the complement system in bacterial meningitis - Koelman, Diederik L H; Brouwer, Matthijs C; van de Beek, Diederik (Brain (London, England : 1878), 2019)
Bacterial meningitis is most commonly caused by Streptococcus pneumoniae and Neisseria meningitidis and continues to pose a major public health threat. Morbidity and mortality of meningitis are driven by an uncontrolled host inflammatory response. This comprehensive update evaluates the role of the complement system in upregulating and maintaining the inflammatory response in bacterial meningitis. Genetic variation studies, complement level measurements in blood and CSF, and experimental work have together led to the identification of anaphylatoxin C5a as a promising treatment target in bacterial meningitis. In animals and patients with pneumococcal meningitis, the accumulation of neutrophils in the CSF was mainly driven by C5-derived chemotactic activity and correlated positively with disease severity and outcome. In murine pneumococcal meningitis, adjunctive treatment with C5 antibodies prevented brain damage and death. Several recently developed therapeutics target C5 conversion, C5a, or its receptor C5aR. Caution is warranted because treatment with C5 antibodies such as eculizumab also inhibits the formation of the membrane attack complex, which may result in decreased meningococcal killing and increased meningococcal disease susceptibility. The use of C5a or C5aR antagonists to specifically target the harmful anaphylatoxins-induced effects, therefore, are most promising and present opportunities for a phase 2 clinical trial.